Intravenous versus intramuscular epinephrine administration during cardiopulmonary resuscitation – a pilot study in piglets. Issue 10 (1st April 2013) - Mauch, Jacqueline; Ringer, Simone K.; Spielmann, Nelly; Weiss, Markus
Abstract: Background: Early epinephrine administration in cardiac arrest seems to be advantageous to achieve return of spontaneous circulation (ROSC). Because intravenous (i.v.) or intraosseous access is not always immediately available, this study compares efficacy of early intramuscular (i.m.) epinephrine administration with early and delayed i.v. epinephrine injection in an animal cardiac arrest model. Methods: Piglets anesthetized with sevoflurane were intoxicated by an i.v. ropivacaine infusion until circulatory arrest. After 1 min basic life support (chest compression and ventilation), epinephrine i.v. (10 μg·kg −1, group IV) or epinephrine i.m. (100 μg·kg −1, group IM) or normal saline (group NS) was applied. Further doses of epinephrine were given in group IV every 4 min and in group IM after 10 min if required. Twenty‐one minutes after circulatory arrest, i.v. epinephrine – as necessary – was given to all animals. Thus, group NS represents late epinephrine administration. Outcomes were survival and time to ROSC. Results: Twenty‐four pigs aged 19.5 (median, interquartile range 16–22) days, weighing 5.4 (5.0–5.7) kg were investigated. Total amount of ropivacaine administered was 8.9 (8.1–10.1) mg·kg −1 . Cardiac rhythm before starting CPR was pulseless electric activity and asystole in 15 and 9 pigs, respectively. Eight, seven, and four pigs survived in group IV, IM, and NS. Focusing on surviving animals, time to ROSC was 2, 4 and 19.5 min in group IV, IM, and NS. Conclusions: Early i.m. epinephrine provided similar survival compared with early i.v. epinephrine and was superior to delayed epinephrine administration in resuscitation of ropivacaine‐induced cardiac arrest in piglets.